Manajemen Hubungan Pelanggan Pada PT. Sejahtera Palembang Furindo Berbasis Website - Dwi Rana Afkar Futhna; Rika Kharlina Ekawati (JuSiTik : Jurnal Sistem dan Teknologi Informasi Komunikasi, 2021)
PT. Sejahtera Palembang Furindo is a company engaged in the distribution of office furniture products. This company serves all customers, both individuals and stores. In the business process of PT. Sejahtera Palembang Furindo currently does not use information technology such as websites in providing services to customers, so customers need a long time because they have to come directly to the company to place an order for products or want to know about prices and products sold. The system design is made in the form of a website, where customers will find it easier to place orders for products. Using an iteration methodology where at each stage can be done repeatedly. The tools that will be used in the system design are PHP, JavaScript, HTML, and use a MySQL database. This system can support the company's service performance to attract new customers and retain existing customers as well as a medium of information for customers.